Bone marrow mesenchymal stem cell-derived exosome uptake and retrograde transport can occur at peripheral nerve endings. Issue 1 (4th December 2019) - Ren, Rui; Tan, Xiao-Hong; Zhao, Jiu-Hong; Zhang, Quan-Peng; Zhang, Xian-Fang; Ma, Zhi-Jian; Peng, Ya-Nan; Liu, Qi-Bing; Zhang, Hai-Ying; Li, Yun-Qing; He, Rui; Zhao, Zhen-Qiang; et al.
Abstract: We investigated the occurrence of mesenchymal stem cell (MSC)-derived exosome uptake and retrograde transport at peripheral nerve endings using bone marrow MSCs (bMSCs) transduced with recombinant CD63-green fluorescent protein (GFP) lentiviral plasmid. GFP was used to track the release of bMSC-derived exosomes and the uptake and transport at peripheral nerve terminals, the dorsal root ganglion (DRG), and the spinal cord. In vitro cell culture and injection of a CD63-GFP exosome suspension into the right gastrocnemius muscle of an in vivo rat model were also performed. Fluorescence microscopy of co-cultured CD63-GFP exosomes and SH-SY5Y or BV2 cell lines and primary cultured DRG cells in a separate experiment demonstrated exosome uptake into DRG neurons and glia. Moreover, we observed both retrograde axoplasmic transport and hematogenous transport of exosomes injected into rat models at the DRG and the ipsilateral side of the anterior horn of the spinal cord using fluorescence microscopy, immunohistochemistry, and Western blot analyses. In conclusion, we showed that exosome uptake at peripheral nerve endings and retrograde transport of exosomes to DRG neurons and spinal cord motor neurons in the anterior horn can occur. In addition, our findings propose a novel drug delivery approach for treating neuronal diseases.